PERAN AHF (AIDS HEALTCARE FOUNDATION) DALAM MENANGANI HIV-AIDS DI INDONESIA PADA TAHUN 2020-2022 - Putri, Marcela Hanindya Putri; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
HIV is a virus that has been a global threat for more than decades. Since it was first discovered in 1920 in the Congo, this virus requires serious cooperation to be handled by all groups. Indonesia is a country that is serious about dealing with HIV problems. NGOs are working together to address the global challenges posed by this disease. In 2020, AHF (AIDS Healthcare Foundation) Indonesia began collaboration with the Ministry of Social Affairs of the Republic of Indonesia for 2020-2023. The focus of the collaboration program between AHF Indonesia and the Ministry of Social Affairs is related to the Social Rehabilitation Program in HIV Prevention, early HIV detection, treatment, therapy and support for People Living with HIV/AIDS (PLWHA). Using qualitative descriptive methods and bibliographic techniques, journals and other official documents. The author proves that NGOs such as AHF (Aids Healthcare Foundation) play a role in overcoming the HIV-AIDS problem in the world, especially Indonesia. Keywords: HIV, AIDS, AHF, Indonesia